2009
DOI: 10.1016/j.pnpbp.2009.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Trait anxiety and ethanol: Anxiolysis in high-anxiety mice and no relation to intake behavior in an addiction model

Abstract: Anxiety has been proposed to play a role in the development of alcohol addiction, but the exact mechanisms by which this occurs remain unclear. The present study aimed to verify the relationship between basal anxiety levels, the anxiolytic-like effect of ethanol, and ethanol intake in mice exposed to an addiction model. In one experiment Swiss mice were characterized as high-anxiety (HA), medium-anxiety (MA), or non-anxiety (NA) in the elevated plus maze and then received saline or ethanol 2 g/kg acutely and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 62 publications
4
23
1
Order By: Relevance
“…A medium level of anxiety, normally observed in rodents, based on the free-exploratory paradigm [23] and EPM test [24], is consistent with the finding of the present study. In the present study, rats displaying medium level of anxiety spent 10-50% of the test time in the open arm of EPM which may be considered as normal anxiety trait in rats according to previous report [20].…”
Section: Discussionsupporting
confidence: 93%
“…A medium level of anxiety, normally observed in rodents, based on the free-exploratory paradigm [23] and EPM test [24], is consistent with the finding of the present study. In the present study, rats displaying medium level of anxiety spent 10-50% of the test time in the open arm of EPM which may be considered as normal anxiety trait in rats according to previous report [20].…”
Section: Discussionsupporting
confidence: 93%
“…Selectively bred rats that show high anxiety in an open field are found to consume more ethanol at concentrations of 6% or 10% (Izidio and Ramos, 2007), but not at 2% or 4% (Da Silva et al, 2004). Further, studies in outbred rodents using an elevated plus maze have also demonstrated a positive relationship (Spanagel et al, 1995), although this was not confirmed in a recent study in Swiss mice (Correia et al, 2009). …”
Section: Introductionmentioning
confidence: 85%
“…Anxiety Classification: The EPM and LDA tests quantify anxiety-related behaviors by creating conditions that tap into the intrinsic conflicts arising from the innate tendency of mice to explore (in order to increase the probability of finding food, water, and sex) and the innate fear/anxiety generated during exploration of well-lit, exposed, or elevated areas, which increases the probability of being attacked or killed by a predator or conspecific aggressor. These arenas have been used to measure trait anxiety in mice [114][116]. We used data from two ethological tests (EPM and LDA) because each test is thought to measure a different dimension of anxiety [92].…”
Section: Methodsmentioning
confidence: 99%